Bilinearization and soliton solutions of N=1 supersymmetric coupled dispersionless integrable system. Issue 1 (2nd January 2017) - Mirza, Arifa; ul Hassan, Mahmood
Abstract : An N =1 supersymmetric generalization of coupled dispersionless (SUSY-CD) integrable system has been proposed by writing its superfield Lax representation. It has been shown that under a suitable variable transformation, the SUSY-CD integrable system is equivalent to N =1 supersymmetric sine-Gordon equation. A superfield bilinear form of SUSY-CD integrable system has been proposed by using super Hirota operator. Explicit expressions of superfield soliton solutions of SUSY-CD integrable system have been obtained by using the Hirota method.